Preventive Governance in Premarital Health Screening Policy: A Local Government Case Study in Kotawaringin Barat, Indonesia - Jumrotunisak, Jumrotunisak; Pelu, Ibnu Elmi A. S. (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes the implementation of the premarital health check policy in Kotawaringin Barat District, Indonesia, through the lens of good governance. Premarital health checks, although normative as a preventive intervention for maternal and child health, depend on the quality of local governance for their effectiveness. Data were collected through in-depth interviews with officials from the Health Office, the Religious Affairs Office, health service providers, and prospective brides and grooms, as well as document analysis. The findings show that this policy reflects the principles of good governance, such as transparency, accountability, participation, effectiveness, and responsiveness. Transparency is evident in the provision of procedural information, but it remains predominantly administrative and lacks substantive health literacy, with beneficiaries viewing the examination more as a formal obligation. Accountability mechanisms exist through standard procedures and interagency coordination, although health-based outcome evaluations are still limited. Community participation is largely compliance-oriented, indicating a need for improved preventive awareness. The integration of health services and marriage registration improves access to preventive services, although challenges remain in institutional capacity, data integration, and results-based monitoring. This study concludes that a shift from administrative compliance to collective awareness of preventive health is necessary for sustainable health improvement. Theoretically, this study contributes to governance theory by conceptualizing preventive governance as an expansion of good governance, integrating prevention-oriented public health objectives into the core dimensions of transparency, accountability, participation, and effectiveness. Strengthening digital governance, health literacy, and performance-based accountability are proposed to increase the policy’s public value impact